Management of Chlamydia Cases in Australia (MoCCA): protocol for a non-randomised implementation and feasibility trial - Rebecca Guy; Marcus Y Chen; Basil Donovan; Jane S Hocking; Natalie Carvalho; Christopher Fairley; Claudia Estcourt; Meredith Temple-Smith; Jane Tomnay; Julie Simpson; David Regan; David Hawkes; et al. (BMJ Open)
Introduction The sexually transmitted infection chlamydia can cause significant complications, particularly among people with female reproductive organs. Optimal management includes timely and appropriate treatment, notifying and treating sexual partners, timely retesting for reinfection and detecting complications including pelvic inflammatory disease (PID). In Australia, mainstream primary care (general practice) is where most chlamydia infections are diagnosed, making it a key setting for optimising chlamydia management. High reinfection and low retesting rates suggest partner notification and retesting are not uniformly provided. The Management of Chlamydia Cases in Australia (MoCCA) study seeks to address gaps in chlamydia management in Australian general practice through implementing interventions shown to improve chlamydia management in specialist services. MoCCA will focus on improving retesting, partner management (including patient-delivered partner therapy) and PID diagnosis.Methods and analysis MoCCA is a non-randomised implementation and feasibility trial aiming to determine how best to implement interventions to support general practice in delivering best practice chlamydia management. Our method is guided by the Consolidated Framework for Implementation Research and the Normalisation Process Theory. MoCCA interventions include a website, flow charts, fact sheets, mailed specimen kits and autofills to streamline chlamydia consultation documentation. We aim to recruit 20 general practices across three Australian states (Victoria, New South Wales, Queensland) through which we will implement the interventions over 12–18 months. Mixed methods involving qualitative and quantitative data collection and analyses (observation, interviews, surveys) from staff and patients will be undertaken to explore our intervention implementation, acceptability and uptake. Deidentified general practice and laboratory data will be used to measure pre-post chlamydia testing, retesting, reinfection and PID rates, and to estimate MoCCA intervention costs. Our findings will guide scale-up plans for Australian general practice.Ethics and dissemination Ethics approval was obtained from The University of Melbourne Human Research Ethics Committee (Ethics ID: 22665). Findings will be disseminated via conference presentations, peer-reviewed publications and study reports.